The Role of Smart Grids in Enhancing Energy Efficiency and Sustainability - Rishaan Bhatia (International Journal of Advanced Control and System Engineering, 2024)
The rapid adoption of smart grid technologies is reshaping the energy sector, prompting significant changes in the traditional utility business model. This survey paper provides a comprehensive analysis of the impact of smart grids on utility revenue streams, focusing on the transition from conventional electricity sales to new, service-oriented business models. By examining key innovations such as energy-as-a-service, virtual power plants, and peer-to-peer energy trading, this study highlights how utilities are leveraging smart grid capabilities to enhance operational efficiency and create new value propositions for consumers. Drawing on an extensive review of academic literature, industry reports, and case studies from various global regions, the paper explores the financial implications of smart grid adoption, including both the opportunities and risks it presents. It identifies critical drivers behind the transformation of utility business models, such as regulatory support, digital infrastructure investment, and the rise of decentralized energy resources. The study also discusses regional variations in smart grid adoption, revealing how market conditions and regulatory frameworks shape the success of different business models. In conclusion, this survey contributes to the understanding of how smart grid technologies are fundamentally altering the utility landscape, offering insights for future research and practical recommendations for utilities and policymakers. By adapting to these changes, utilities can position themselves to thrive in an increasingly decentralized, digital, and dynamic energy market. The paper also identifies gaps in the existing literature, suggesting areas for further exploration, particularly in long-term financial sustainability and regulatory innovation.
Keywords: Smart grids; consumers; energy-as-a-service; regulatory condition; virtual power plants